2017
DOI: 10.1002/psc.2963
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient-derived high and low phosphatidylserine-exposing colorectal carcinoma cells in their interaction with anti-cancer peptides

Abstract: Current cancer treatment is frequently compromised by severe adverse effects on healthy cells and tissues as well as by the increasing burden of (multi-)drug resistances. Some representatives of small, amphipathic peptides known as host defense peptides possess the potential to overcome these limitations and to evolve as future anti-cancer therapeutics. Peptide NK-2, derived from porcine NK-lysin, was originally discovered due to its broad-spectrum antimicrobial activities. Today, also potent anti-cancer activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Human A375 melanoma cells that express 50-fold more PS than noncancerous HaCaT cells binds to the A375 melanoma cells with higher affinity for the membranolytic peptide temporin-1CEa ( Wang et al, 2016 ). Similarly, the membranolytic peptide NK2 exhibits preferential interaction with colorectal cancer cell lines ( Wilms and Andrä, 2017 ). Matrix metalloproteinase 2 (MMP2)-sensitive PS-modified nanoparticles were developed to target Tumor-associated macrophages (TAMs) in the tumor microenvironments.…”
Section: Targeting the Ps On Malignant Cells For Anti-cancer Therapeu...mentioning
confidence: 99%
“…Human A375 melanoma cells that express 50-fold more PS than noncancerous HaCaT cells binds to the A375 melanoma cells with higher affinity for the membranolytic peptide temporin-1CEa ( Wang et al, 2016 ). Similarly, the membranolytic peptide NK2 exhibits preferential interaction with colorectal cancer cell lines ( Wilms and Andrä, 2017 ). Matrix metalloproteinase 2 (MMP2)-sensitive PS-modified nanoparticles were developed to target Tumor-associated macrophages (TAMs) in the tumor microenvironments.…”
Section: Targeting the Ps On Malignant Cells For Anti-cancer Therapeu...mentioning
confidence: 99%
“…Circular dichroism (CD) spectroscopic studies, as well as zeta-potential and particle size measurements, were employed to study peptide-membrane interactions as a function of various physico-chemical properties, membrane compositions and peptide sequences [29,30,31]. Binding studies and encapsulation experiments using the two most commonly employed methods for the lab-scale preparation of peptide-loaded liposomes (i.e., thin-film hydration and microfluidic mixing), were then used to test whether the extent of electrostatic binding translates to corresponding levels of encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed its beneficial effect in lung, ovarian, colorectal, and gastric cancer [6][7][8]. In addition, dietary supplements containing ascorbic acid, lysine, proline, and green tea extracts are known to reduce the tumor growth in vivo studies [9][10][11][12]. Micromolar concentration of extracellular Vitamin C kills cancer cells but not normal cells in an H 2 O 2 -dependent manner [13].…”
Section: Introductionmentioning
confidence: 99%